Prospective trial to evaluate the prognostic value of different nutritional assessment scores for survival in pancreatic ductal adenocarcinoma (NURIMAS Pancreas SURVIVAL). Issue 6 (20th September 2021) - Heckler, Max; Klaiber, Ulla; Hüttner, Felix J.; Haller, Sebastian; Hank, Thomas; Nienhüser, Henrik; Knebel, Philip; Diener, Markus K.; Hackert, Thilo; Büchler, Markus W.; Probst, Pascal
Abstract: Background: Malnutrition is associated with poor survival in pancreatic cancer patients. Nutritional scores show great heterogeneity diagnosing malnutrition. The aim of this study was to find the score best suitable to identify patients with malnutrition related to worse survival after surgery for pancreatic ductal adenocarcinoma (PDAC). This study represents a follow‐up study to the prospective NURIMAS Pancreas trial that evaluated short term impact of nutritional score results after surgery. Methods: Risk of malnutrition was evaluated preoperatively using 12 nutritional assessment scores. Patients were followed‐up prospectively for at least 3 years. Patients at risk for malnutrition were compared with those not at risk according to each score using Kaplan–Meier survival statistics. Results: A total of 116 patients receiving a PDAC resection in curative intent were included. Malnutrition according to the Subjective Global Assessment score (SGA), the Short Nutritional Assessment Questionnaire (SNAQ), and the INSYST2 score was associated with worse overall survival (SGA: at‐risk: 392 days; not at‐risk: 942 days; P = 0.001; SNAQ: at‐risk: 508 days; not at‐risk: 971 days; P = 0.027; INSYST2: at‐risk: 538 days; not at risk: 1068; P = 0.049). In the multivariate analysis, SGA (hazard ratio of death 2.16, 95% confidence interval 1.34–3.47, P = 0.002) was associated with worse overall survival. Conclusions: Malnutrition as defined by the Subjective Global Assessment is independently associated with worse survival in resected PDAC patients. The SGA should be used to stratify PDAC patients in clinical studies. Severely malnourished patients according to the SGA profit from intensified nutritional therapy should be evaluated in a randomized controlled trial.